Hydrogenation of crotonaldehyde on Pt/SiO2 catalysts modified with tin added via surface organometallic chemistry on metals techniques - Santori, Gerardo Fabian (2000)
The importance of the preparation procedure and the understanding of the mechanisms that control this stage on the final properties of the catalyst are evidenced for PtSn systems obtained via surface organometallic chemistry on metals (SOMC/M) techniques. The temperature of preparation reaction also plays a fundamental role as regards the nature of the active phase finally obtained, giving rise to catalytic phases having different levels of selectivity to unsaturated alcohols (UOL) in the crotonaldehyde hydrogenation. Organobimetallic catalysts lead to very high selectivities to crotyl alcohol (80% at 5% conversion).